Chemical differences between long and short amosite asbestos: differences in oxidation state and coordination sites of iron, detected by infrared spectroscopy. Issue 9 (1st September 1999) - Graham, A; Higinbotham, J; Allan, D; Donaldson, K; Beswick, P H
Abstract : OBJECTIVES: Short fibres of amosite asbestos (SFA), obtained by ball milling of long fibres (LFA), have been shown to be less pathogenic than long fibres. Accumulating evidence suggests an important role for differences in surface chemistry between fibres. Iron has been implicated in the pathogenesis of asbestos fibres. In this study infrared (IR) spectroscopy was used to compare LFA and SFA in terms of the coordination and oxidation state of iron at the three cation sites (M1, M3, M1). METHODS: Infrared was used to examine LFA ad SFA, when dry and when hydrated in the presence and absence of the chelators desferroxamine and ferrozine. With appropriate software the proportions of iron and its oxidation states in the overlapping peaks were resolved and assigned, and the three coordination sites were identified. Data were obtained from 10 samples of both lengths of fibre for each of the four treatments. Iron release was also monitored. RESULTS: Iron was significantly more oxidised in LFA than SFA. Further oxidation of the dry fibres with water, ferrozine, or desferroxamine tended to abolish these differences. There were also significant differences between the proportions of iron held in the different coordination sites of the fibres. For LFA, a higher proportion of its iron was held in the cation sites coordinating less with iron and more with Mg. Interestingly, the sites coordinating single irons were significantly more oxidised than multiple sites. The single iron sites were more oxidised in LFA than SFA and were more readily oxidised by the treatments. CONCLUSIONS: Important chemical differences between LFA and SFA were found. There seemed to be some mobility of iron near the surface. Based on these data it is speculated that the 1 iron surface site may be important in pathogenesis.